A contact material surface coating and treatment method thereof
By adopting a double-layer structure plating treatment method on low-tungsten copper-tungsten alloy contacts, a uniform first plating layer and protective silver plating are formed by sintering electroless plating and electroplating, the problem of contacts being affected by arc in high-voltage opening and closing circuits is solved, significantly improving wear resistance and conductivity, extending service life and reducing production costs.
Patent Information
- Application Number
- CN202510142044.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-02-10
AI Technical Summary
Low tungsten copper-tungsten alloy contacts are easily affected by arc in high-voltage opening and closing circuits, resulting in plating wear and internal copper oxidation, shortening service life.
The plating treatment method with a double-layer structure is adopted, and the first and second plating layers are obtained by sintering electroless plating and electroplating, and the gel liquid is formed by reacting graphene oxide with supramolecular crosslinking agent. As the carrier of magnesium diboride fine powder, a first plating layer with uniform texture is formed by heat treatment, and a protective silver plating layer is formed during the electroplating process.
The wear resistance and conductivity of the contacts are significantly improved, the wear of the plating layer and the oxidation of the copper inside are suppressed, the service life of the contacts is extended, and the production cost of the plating is reduced.
Smart Images

Figure CN119592952B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of contact material plating, and more specifically, to a contact material surface plating and a processing method thereof. Background Art
[0002] Contacts are one of the key components of switchgear, and are mainly used to connect and disconnect circuits. According to different application scenarios, they can be divided into high-voltage contacts and low-voltage contacts. The metal materials commonly used as contacts are mainly copper, silver, copper-silver alloys, and their metal-doped nickel and tungsten alloys. Due to the high price of silver metal, the contacts of non-precious instruments in industry are mainly copper-tungsten alloys.
[0003] Copper-tungsten alloy has excellent electrical conductivity and wear resistance, and as the tungsten content in the alloy increases, the alloy's wear resistance improves significantly. However, due to the high cost of copper-tungsten alloys with high tungsten content, industrial production has gradually developed towards low-tungsten contact materials. Due to the limitations of material properties, this low-tungsten copper-tungsten contact is easily affected by arcs when used in high-voltage switching circuits.
[0004] At the moment of circuit disconnection, due to the sudden decrease in the contact area of the conductor at the contact, the contact resistance increases instantly, and there is a certain probability of breaking through the air and generating an arc. The instantaneous temperature of the excited arc can reach thousands of degrees Celsius, which is much higher than the melting point of copper, resulting in the loss of copper at the arc striking point on the contact due to gasification and evaporation. Under long-term action, a gap will be left on the contact, which is not conducive to the long-term use of the contact. In addition, the surface structure of the gap is more conducive to arc concentration. The process of contact connection and disconnection continuously wears the contact and exposes the inner copper layer. The oxidation rate of copper is accelerated under electrical and thermal conditions, greatly shortening the service life of the contact. In order to further extend the service life of the contact, a coating method is usually used to coat a protective layer of metal and its alloy on the surface of the contact to protect the inner alloy. However, the coating materials and effects that can be used to protect copper-tungsten alloys are relatively limited, and wear and internal copper oxidation problems will still occur after a period of use.
[0005] The Chinese patent application document with publication number CN116417268A discloses a high-voltage disconnector contact with a long service life. In the application, a layer of silver powder is sprayed on a pure copper substrate by a melting plating process, and a protective layer is obtained after melting. Through the treatment, an interdiffusion zone is set between the copper substrate and the protective layer, and a short rod-shaped silver precipitation phase is obtained in this area. By adjusting the grain size of the precipitation phase, a protective coating with good wear resistance and conductivity is finally obtained.
[0006] Although the above application documents have improved the wear resistance of the contacts to a certain extent, this improvement is relatively limited. Once the plating is damaged, the gap will continue to grow, eventually reducing the protective effect of the plating on the contacts. In addition, the plating used in the application is mainly pure silver, which has a high production cost. Therefore, there is still a need to find a method to inhibit plating wear and reduce plating production costs. Summary of the invention
[0007] In order to further obtain a coating with low wear and low production cost, the present application provides a contact material surface coating and a processing method thereof.
[0008] In a first aspect, the present application provides a method for treating a surface coating of a contact material, wherein the surface coating is a double-layer structure obtained by sintering chemical plating and electroplating, respectively, and comprises the following steps:
[0009] [S01] Sintering chemical plating: take the alloy rod for pretreatment, spray the slurry with a spray gun, then heat treat it under an argon protective gas environment, and let it stand overnight at room temperature to obtain the first coating;
[0010] [S02] Electroplating: The alloy rod after sintering and chemical plating is placed in an electrolytic cell as the cathode, and the silver sheet is used as the anode, and electroplated in the plating solution to obtain the second plating layer.
[0011] Preferably, in step [S01], the pretreatment is: taking the alloy rod, sanding it, alkali immersion, adjusting the temperature to 50-60°C, water bathing for 3-5 minutes, then placing it in anhydrous ethanol, ultrasonic cleaning for 15-20 minutes, isolating it from oxygen and drying it at room temperature for storage.
[0012] By adopting the above technical solution, the surface grease and oxide layer can be removed by pre-treating the alloy rod, so that the composite effect of the coating and the alloy rod is optimal during the subsequent coating operation.
[0013] Preferably, in step [S01], the treatment slurry is prepared by mixing the following raw materials in parts by mass: 50-75 parts of a mixed solvent, 10-15 parts of magnesium diboride powder, 0.5-1 parts of sodium silicate, and 0.01-0.02 parts of graphene oxide, comprising the following steps:
[0014] Take graphene oxide, add mixed solvent, disperse, adjust the temperature to 70-85°C, treat for 5-6h, then add magnesium diboride powder and sodium silicate to the system, adjust the pH to 7.2-7.5, continue to treat, then vacuumize at 0.01Mpa, and obtain the treated slurry after exhausting.
[0015] By adopting the above technical solution, the surface hydroxyl, carboxyl and other functional groups of graphene oxide react with the mixed solvent in a heated environment, cross-linking into a network, and a gel liquid with a certain adhesiveness is obtained after treatment, which can be used as a carrier of magnesium diboride micropowder. The subsequent spray gun spraying operation can load the magnesium diboride micropowder onto the surface of the alloy rod, and obtain the first coating by heat treatment. The added sodium silicate is hydrolyzed in a weakly alkaline environment, and a small amount of silicon dioxide is obtained after heat treatment, which is mixed in the magnesium diboride to inhibit the growth of grains during the melting and cooling process of the magnesium diboride, thereby obtaining magnesium diboride crystals with smaller particle size.
[0016] Preferably, the mixed solvent is prepared by mixing water, anhydrous ethanol, polyvinyl pyrrolidone, polyvinyl alcohol and sodium carbonate in a mass volume ratio of (45-47) ml: (5-7) ml: (3-3.5) g: (1.2-1.5) g: (0.5-1) g.
[0017] By adopting the above technical scheme, in the mixed solvent, polyvinyl pyrrolidone and polyvinyl alcohol as supramolecular crosslinking agents can react with graphene oxide to promote the formation of a gel network, and sodium carbonate as a dispersant for magnesium diboride micropowder can make the dispersion of magnesium diboride micropowder in the mixed system more uniform.
[0018] Preferably, the preparation of the magnesium diboride powder comprises the following steps:
[0019] [A01] Take magnesium powder, mix it with boron powder, grind it, press it into tablets under a pressure of 30-32 MPa, put it into a tube furnace, calcine it with argon gas, cool it to room temperature, and crush it in a mortar to obtain magnesium diboride particles;
[0020] [A02] Magnesium diboride particles are placed in anhydrous ethanol and ball-milled to control the ball-to-material ratio to (3-4):1. After air-drying and sieving, magnesium diboride powder is obtained.
[0021] By adopting the above technical solution, magnesium powder and boron powder are mixed and pressed into sheets, and then reacted at high temperature to obtain magnesium diboride particles. By further ball milling, magnesium diboride micropowder with a smaller particle size can be obtained, which is helpful for dispersing magnesium diboride in the gel solution and obtaining a more uniform coating.
[0022] Preferably, in step [A02], the average particle size of the boron powder is 0.1 micrometer.
[0023] Preferably, in step [A02], the average particle size of the magnesium diboride powder obtained after ball milling and sieving is 1.2 microns.
[0024] By adopting the above technical solution, the first coating layer prepared by using magnesium diboride micropowder with this particle size has the best effect.
[0025] Preferably, in step [S01], the heat treatment comprises the following steps: fixing the alloy rod with the surface sprayed with the treatment slurry with a bracket, suspending it in an oven, adjusting the temperature to 150-175°C, drying it for 10-15 minutes, then transferring it to a muffle furnace, adjusting the temperature to 835-840°C, firing it for 2-2.5 minutes, and then transferring it to an oven at 100°C for treatment for 1.5-2 hours.
[0026] By adopting the above technical solution, the solvent part in the treatment slurry can be removed by oven drying, which is conducive to the formation of subsequent coating. During the muffle furnace firing process, magnesium diboride and other solid components in the treatment slurry melt and adhere to the alloy rod to form a sintered film. After cooling, the first coating can be obtained to protect the inner layer of copper-tungsten alloy.
[0027] Preferably, the average thickness of the first coating is 25 microns, and the average thickness of the second coating is 32 microns.
[0028] By adopting the above technical solution, the thickness of the first coating and the second coating is regulated, and the copper-tungsten alloy surface coating combination effect is optimal.
[0029] In the second aspect, the present application obtains a surface coating through the above technical solution.
[0030] In summary, this application has the following beneficial effects:
[0031] 1. The present application uses a gel solution obtained by reacting graphene oxide with a supramolecular crosslinking agent as a liquid carrier of magnesium diboride micropowder, and a uniform first coating structure can be obtained after heat treatment. The gelled graphene oxide is tightly attached to the alloy rod after heat treatment to obtain a carbon film, which can improve the adhesion of magnesium diboride to the alloy rod.
[0032] 2. In this application, it is preferred to use homemade magnesium diboride powder as a component of the treatment slurry, and obtain the first coating by heat treatment. During use, when the second coating is damaged and the scratch continues to extend to the inside of the coating, the grinding and cutting effect causes the magnesium diboride in the first coating to be converted into microcrystals and distributed between the contact surface of the alloy and the ground object, which acts as a self-lubricating agent, inhibiting further damage to the coating and exposing the copper part inside the alloy rod. At the same time, due to the concentration of the arc at the notch, under the action of the intermittent instantaneous high-temperature arc, a part of the magnesium diboride decomposes and quickly forms a eutectic alloy with copper and silver with similar melting points. The magnesium element in the alloy has a higher oxidation activity than copper, and competes with copper for the oxygen element in the oxidation reaction, thereby inhibiting the oxidation of copper. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a SEM image of the cross-section of the coated alloy rod in Example 2 of the present application.
[0034] Figure 2These are the test results of the coating friction coefficient and wear groove depth of Examples 1-3 of the present application and Comparative Examples 1-2.
[0035] Figure 3 These are the test results of the coating contact resistance of Examples 1-3 and Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION
[0036] The surface coatings prepared in Example 1-3 and Comparative Example 1-2 are double-layer structures, which are obtained by sintering chemical plating and electroplating in sequence, wherein the first coating is obtained by sintering chemical plating, and the second coating is obtained by electroplating.
[0037] Example 1
[0038] The steps for preparing the contact surface coating in this embodiment are as follows:
[0039] [S01] Sintering chemical plating: Take an alloy rod with a size of 10mm×5mm×30mm, polish it with 800-grit sandpaper, immerse the alloy rod in 0.1mol / L sodium hydroxide solution, adjust the temperature to 50℃, and place it in a water bath for 3min to remove surface grease and oxide layer. Then, place the alloy rod in anhydrous ethanol for ultrasonic cleaning for 15min, isolate it from oxygen and dry it at room temperature. After it is fully dried, use a liquid spray gun to evenly spray a layer of treatment slurry on the alloy rod. After spraying, fix the alloy rod with a metal bracket, suspend it in a 150℃ oven, and dry it for 10min. Then, transfer the alloy rod with preliminary surface drying to a muffle furnace at 835℃ in an argon protective gas atmosphere and sinter it for 2min. Then, transfer it to a 100℃ oven for treatment for 1.5h, maintain the argon atmosphere, and obtain the first coating with an average film thickness of 25μm at room temperature overnight.
[0040] [S02] Electroplating: The alloy rod after sintering chemical plating is placed in an electrolytic cell as the cathode, and a silver sheet with a purity of 99.99% is used as the anode. Electroplating is carried out in the plating solution, and the current density is controlled to be 0.65A / dm 2 , stirring speed 500 rpm, temperature 35°C, lasting 2 hours, to obtain a second coating with an average film thickness of 32 microns.
[0041] In this embodiment, the treatment slurry is prepared by mixing 50g of mixed solvent, 10g of magnesium diboride powder, 0.5g of sodium silicate, and 0.01g of graphene oxide, and the specific steps are as follows:
[0042] Take graphene oxide, add it to the mixed solvent, adjust the magnetic stirring speed to 50 rpm, the temperature to 70°C, and treat for 5 hours, then add magnesium diboride powder and sodium silicate to the system, adjust the pH to 7.2, the magnetic stirring speed to 100 rpm, and continue to treat for 2.5 hours to obtain a glue solution, then evacuate the glue solution at 0.01 MPa, let it stand for 1 hour to exhaust, and obtain a treated slurry.
[0043] The preparation steps of magnesium diboride powder in this embodiment are as follows:
[0044] [A01] Take 8 g of magnesium powder, mix it with 21 g of boron powder, grind it for 1 min to obtain a mixed powder, then adjust the pressure of the powder tablet press to 30 MPa, press the mixed powder into tablets, put it into a tubular furnace, and heat the furnace to 700°C at a temperature gradient of 4°C / min under argon atmosphere, then keep it warm for 0.5 h, cool it naturally at room temperature, and crush it in a mortar for 3 min to obtain magnesium diboride particles.
[0045] [A02] Take 12g of magnesium diboride particles, mix with anhydrous ethanol and then ball mill, control the ball-to-material ratio to 3:1, grind for 2h, air-dry and sieve to obtain magnesium diboride micropowder with an average particle size of 1.2 microns.
[0046] Among them, the composition of the alloy rod is 35% tungsten, 64.5% copper, and the remainder is impurities. The plating solution is prepared by mixing 30g / L silver nitrate, 80g / L ammonium acetate, 40g / L potassium hydroxide, 10g / L ammonia water, and 5g / L ethylenediamine. The mixed solvent is prepared by mixing water, anhydrous ethanol, polyvinyl pyrrolidone, polyvinyl alcohol, and sodium carbonate in a mass volume ratio of 45ml:5ml:3g:1.2g:0.5g. Graphene oxide (industrial grade, purity>97%) was provided by Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences. Boron powder (average particle size 0.1 micron, purity 99.9%) was provided by Beijing Dekedaojin Technology Co., Ltd.
[0047] Example 2
[0048] The steps for preparing the contact surface coating in this embodiment are as follows:
[0049] [S01] Sintering chemical plating: Take an alloy rod with a size of 10mm×5mm×30mm, polish it with 800-mesh sandpaper, immerse the alloy rod in 0.1mol / L sodium hydroxide solution, adjust the temperature to 55℃, and place it in a water bath for 3min to remove the surface grease and oxide layer. Then, place the alloy rod in anhydrous ethanol for ultrasonic cleaning for 15min, isolate it from oxygen and dry it at room temperature. After it is fully dried, use a liquid spray gun to evenly spray a layer of treatment slurry on the alloy rod. After spraying, fix the alloy rod with a metal bracket, suspend it in a 150℃ oven, and dry it for 15min. Then, transfer the alloy rod with the preliminary dried surface to a muffle furnace at 835℃ under an argon protective gas atmosphere and sinter it for 2.5min. Then, transfer it to a 100℃ oven for treatment for 2h, maintain the argon atmosphere, and get the first coating with an average film thickness of 25μm at room temperature overnight.
[0050] [S02] Electroplating: The alloy rod after sintering chemical plating is placed in an electrolytic cell as the cathode, and a silver sheet with a purity of 99.99% is used as the anode. Electroplating is carried out in the plating solution, and the current density is controlled to be 0.67A / dm 2 , stirring speed 525rpm, temperature 40℃, lasting 2h, to obtain a second coating with an average film thickness of 32 microns.
[0051] In this embodiment, the treatment slurry is prepared by mixing 65g of mixed solvent, 12g of magnesium diboride powder, 0.75g of sodium silicate, and 0.02g of graphene oxide, and the specific steps are as follows:
[0052] Take graphene oxide, add it to the mixed solvent, adjust the magnetic stirring speed to 75 rpm, the temperature to 85°C, and treat for 5 hours. Then add magnesium diboride powder and sodium silicate to the system, adjust the pH to 7.3, the magnetic stirring speed to 125 rpm, and continue to treat for 2.5 hours to obtain a glue solution. Then, evacuate the glue solution at 0.01 MPa, let it stand for 1.5 hours to exhaust, and obtain a treated slurry.
[0053] The preparation steps of magnesium diboride powder in this embodiment are as follows:
[0054] [A01] Take 9 g of magnesium powder, mix it with 22 g of boron powder, grind it for 2 min to obtain a mixed powder, then adjust the pressure of the powder tablet press to 30 MPa, press the mixed powder into tablets, put it into a tubular furnace, and heat the furnace to 725°C at a temperature gradient of 5°C / min under argon atmosphere, then keep it warm for 1 h, cool it naturally at room temperature, and crush it in a mortar for 3 min to obtain magnesium diboride particles.
[0055] [A02] Take 15g of magnesium diboride particles, mix with anhydrous ethanol and then ball mill, control the ball-to-material ratio to 4:1, grind for 2.5h, air-dry and sieve to obtain magnesium diboride micropowder with an average particle size of 1.2 microns.
[0056] Among them, the composition of the alloy rod is 35% tungsten, 64.5% copper, and the rest is impurities. The plating solution is prepared by mixing 35g / L silver nitrate, 82g / L ammonium acetate, 40g / L potassium hydroxide, 12g / L ammonia water, and 7g / L ethylenediamine. The mixed solvent is prepared by mixing water, anhydrous ethanol, polyvinyl pyrrolidone, polyvinyl alcohol, and sodium carbonate in a mass volume ratio of 45ml:6ml:3.5g:1.5g:1g. Graphene oxide (industrial grade, purity>97%) was provided by Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences. Boron powder (average particle size 0.1 micron, purity 99.9%) was provided by Beijing Dekedaojin Technology Co., Ltd.
[0057] Example 3
[0058] The steps for preparing the contact surface coating in this embodiment are as follows:
[0059] [S01] Sintering chemical plating: Take an alloy rod with a size of 10mm×5mm×30mm, polish it with 800-mesh sandpaper, immerse the alloy rod in 0.1mol / L sodium hydroxide solution, adjust the temperature to 60℃, and place it in a water bath for 5min to remove the surface grease and oxide layer. Then, place the alloy rod in anhydrous ethanol for ultrasonic cleaning for 20min, isolate it from oxygen and dry it at room temperature. After it is fully dried, use a liquid spray gun to evenly spray a layer of treatment slurry on the alloy rod. After spraying, fix the alloy rod with a metal bracket, suspend it in a 175℃ oven, and dry it for 15min. Then, transfer the alloy rod with the preliminary dried surface to a muffle furnace at 840℃ under an argon protective gas atmosphere and sinter it for 2.5min. Then, transfer it to a 100℃ oven for treatment for 2h, maintain the argon atmosphere, and get the first coating with an average film thickness of 25μm at room temperature overnight.
[0060] [S02] Electroplating: The alloy rod after sintering chemical plating is placed in an electrolytic cell as the cathode, and a silver sheet with a purity of 99.99% is used as the anode. Electroplating is carried out in the plating solution, and the current density is controlled to be 0.68A / dm 2 , stirring speed 550rpm, temperature 42°C, lasting 2.2h, to obtain a second coating with an average film thickness of 32 microns.
[0061] In this embodiment, the treatment slurry is prepared by mixing 75g of mixed solvent, 15g of magnesium diboride powder, 1g of sodium silicate, and 0.02g of graphene oxide, and the specific steps are as follows:
[0062] Take graphene oxide, add it to the mixed solvent, adjust the magnetic stirring speed to 75 rpm, the temperature to 85°C, and treat for 6 hours, then add magnesium diboride powder and sodium silicate to the system, adjust the pH to 7.5, the magnetic stirring speed to 150 rpm, and continue to treat for 3 hours to obtain a glue solution, then evacuate the glue solution at 0.01 MPa, let it stand for 2 hours to exhaust, and obtain a treated slurry.
[0063] The preparation steps of magnesium diboride powder in this embodiment are as follows:
[0064] [A01] Take 10g of magnesium powder, mix it with 22.5g of boron powder, grind it for 2min to obtain a mixed powder, then adjust the pressure of the powder tablet press to 32Mpa, press the mixed powder into tablets, put it into a tubular furnace, and heat the furnace to 750℃ at a temperature gradient of 5℃ / min under argon atmosphere, then keep it warm for 1h, cool it naturally at room temperature, and grind it in a mortar for 5min to obtain magnesium diboride particles.
[0065] [A02] Take 15g of magnesium diboride particles, mix with anhydrous ethanol and then ball mill, control the ball-to-material ratio to 4:1, grind for 2.5h, air-dry and sieve to obtain magnesium diboride micropowder with an average particle size of 1.2 microns.
[0066] Among them, the composition of the alloy rod is 35% tungsten, 64.5% copper, and the rest is impurities. The plating solution is mixed with 35g / L silver nitrate, 85g / L ammonium acetate, 45g / L potassium hydroxide, 12g / L ammonia water, and 10g / L ethylenediamine. The mixed solvent is mixed with water, anhydrous ethanol, polyvinyl pyrrolidone, polyvinyl alcohol, and sodium carbonate in a mass volume ratio of 47ml:7ml:3.5g:1.5g:1g. Graphene oxide (industrial grade, purity>97%) was provided by Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences. Boron powder (average particle size 0.1 micron, purity 99.9%) was provided by Beijing Dekedaojin Technology Co., Ltd.
[0067] Comparative Example
[0068] Comparative Example 1
[0069] The difference between this comparative example and Example 1 is that the mixed solvent is prepared by mixing water, anhydrous ethanol, and magnesium aluminum silicate in a mass volume ratio of 50 ml:8 ml:5 g.
[0070] Among them, magnesium aluminum silicate (industrial grade, content 99%) is provided by Lingshou County Sinopec Hengda Mineral Products Processing Plant.
[0071] The remaining steps are the same as those in Example 1.
[0072] Comparative Example 2
[0073] The difference between this comparative example and Example 1 is that an equal amount of silicon dioxide powder is used instead of magnesium diboride powder.
[0074] The average particle size of the silica powder is 1 micron.
[0075] The remaining steps are the same as those in Example 1.
[0076] Performance testing
[0077] SEM Testing
[0078] Take the coated alloy rod of Example 2 and perform SEM scanning test on the coating cross section. The SEM scanning results are as follows: Figure 1 As shown, it can be seen that the bottom layer is the copper-tungsten alloy rod base layer; the middle layer is the first coating layer with an average film thickness of 25 microns; and the top layer is the second coating layer with an average film thickness of 32 microns.
[0079] Friction coefficient and wear groove depth test
[0080] The self-lubricating effect of the surface coating of the plated alloy rods prepared in the scheme is mainly reflected in the first coating. Since the outermost layer of each plated alloy rod is a silver coating, direct friction testing cannot well demonstrate the difference in friction effects of each group. Therefore, the plated alloy rods need to be de-silvered to expose the internal first coating.
[0081] Silver plating removal: Use sandpaper to gently polish and remove the silver plating on the surface of each combination-plated gold rod as a test sample.
[0082] The wear resistance of the coating was tested using a friction and wear tester (model: HKW-2000). The test conditions were dry friction, the motor reciprocating frequency was 2Hz (24mm / s), the load was 5N, the stroke was 6mm, the time was 60min, and the room temperature friction used a steel ball as the grinding body; the grinding groove depth was measured using the pressure-sensitive stylus provided by the equipment. The same area of the coated alloy rods of each embodiment and the comparative example was tested, and the average value of the three tests was taken as the final data of the friction coefficient and grinding groove depth test of each group.
[0083] Contact resistance test
[0084] In the actual contact plugging and disconnecting operation, the copper metal part of the contact is oxidized due to arc striking, and high-resistance copper oxide is continuously generated, which eventually leads to a significant increase in resistance. The degree of copper oxidation can be shown by monitoring the change in contact resistance after the arc treatment test of the coated alloy rod.
[0085] Use an electrical contact material tester (model: JF04D) to conduct a contact closing and opening test, and set the test parameters as follows:
[0086] Test conditions I: voltage 350V, DC 75A, number of operations 1×10 5 times; control the contact pressure to 40N.
[0087] Test conditions II: voltage 450V, DC 80A, number of operations 1×10 5 times; control the contact pressure to 40N.
[0088] A direct current resistance tester (model: FLDZR) was used to test the contact resistance of the coated alloy rods of each group of embodiments and comparative examples after being treated under the two test conditions.
[0089] Analyze Examples 1-3 and Comparative Examples 1-2 and combine Figure 2It can be seen that the surface coating obtained by the embodiment scheme has a low friction coefficient and a grinding groove depth, indicating that under the test conditions, when the first coating of the embodiment scheme is destroyed by the grinding body, a self-lubricating substance is produced to prevent further wear. Specifically, it can be explained that the magnesium diboride microcrystals attached to the surface of the coated alloy rod are transferred from the coating to the contact surface between the coating and the grinding body, reducing the friction coefficient of the contact surface and preventing the continued destruction of the coating. In contrast, the combination effect of comparative example 1 obtained by using magnesium aluminum silicate with a thickening effect instead of the co-gel effect of the supramolecular crosslinking agent and graphene oxide is not as good as that of the embodiment scheme. Among the 5 groups of test schemes, the comparative example 2 scheme has the worst effect in the same group. This may be because comparative example 2 uses silicon dioxide powder instead of magnesium diboride powder, and silicon dioxide powder cannot melt and participate in film formation under the heat treatment temperature conditions, resulting in poor bonding between the first coating obtained after cooling and the alloy rod. During the test, the abrasive is more likely to scratch the coating, which significantly reduces the wear resistance of the coating.
[0090] Analyze Examples 1-3 and Comparative Examples 1-2 and combine Figure 3 It can be seen that among the five groups of test data, the contact resistance measured under each test condition in Comparative Example 2 is the largest, indicating that the oxidation of copper on the plated alloy rod in Comparative Example 2 is the most severe. Analyzing the differences between the scheme of Comparative Example 2 and other test schemes, the violent oxidation of copper in the scheme of Comparative Example 2 is likely related to the formation of the Mg content in the new alloy due to the arc action during the contact closing and opening test process of each group. In Examples 1-3 and Comparative Example 1, a certain amount of Mg element generated by the decomposition of magnesium diboride exists in the generated alloy phase. When the oxidation reaction occurs, the Mg element can compete with the copper in the plated alloy rod for oxygen, thereby inhibiting the oxidation of copper. Among them, among the five groups of test experiments, the schemes of Example 2 and Example 3 have the best effect in inhibiting copper oxidation.
[0091] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for treating a surface coating of a contact material, characterized in that: The surface coating is a double-layer structure, which is obtained by sintering chemical plating and electroplating, and includes the following steps: [S01] Sintering chemical plating: take the alloy rod for pretreatment, spray the slurry with a spray gun, then heat treat it under an argon protective gas environment, and let it stand overnight at room temperature to obtain the first coating; [S02] Electroplating: placing the alloy rod after sintering chemical plating in an electrolytic cell as a cathode, with a silver sheet as an anode, and electroplating in a plating solution to obtain a second plating layer; The treatment slurry is prepared by mixing the following raw materials in parts by mass: 50-75 parts of a mixed solvent, 10-15 parts of magnesium diboride powder, 0.5-1 parts of sodium silicate, and 0.01-0.02 parts of graphene oxide, and comprises the following steps: Take graphene oxide, add a mixed solvent, disperse, adjust the temperature to 70-85°C, treat for 5-6 hours, then add magnesium diboride powder and sodium silicate to the system, adjust the pH to 7.2-7.5, continue to treat, then evacuate at 0.01Mpa, and obtain a treated slurry after exhausting; The mixed solvent is prepared by mixing water, anhydrous ethanol, polyvinyl pyrrolidone, polyvinyl alcohol and sodium carbonate in a mass volume ratio of (45-47) ml: (5-7) ml: (3-3.5) g: (1.2-1.5) g: (0.5-1) g.
2. A method for processing a surface coating of a contact material according to claim 1, characterized in that: In the step [S01], the pretreatment is: taking the alloy rod, grinding with sandpaper, alkali immersion, adjusting the temperature to 50-60°C, water bathing for 3-5 minutes, then placing it in anhydrous ethanol, ultrasonic cleaning for 15-20 minutes, isolating it from oxygen and drying it at room temperature for storage.
3. The method for processing the surface coating of a contact material according to claim 1, characterized in that: The preparation of the magnesium diboride powder comprises the following steps: [A01] Take magnesium powder, mix it with boron powder, grind it, press it into tablets under a pressure of 30-32 MPa, put it into a tube furnace, calcine it with argon gas, cool it to room temperature, and crush it in a mortar to obtain magnesium diboride particles; [A02] Magnesium diboride particles are placed in anhydrous ethanol and ball-milled to control the ball-to-material ratio to (3-4):
1. After air-drying, the particles are sieved to obtain magnesium diboride powder.
4. A method for processing a surface coating of a contact material according to claim 3, characterized in that: In the step [A02], the average particle size of the magnesium diboride powder obtained after ball milling and sieving is 1.2 microns.
5. The method for processing the surface coating of a contact material according to claim 1, characterized in that: In the step [S01], the heat treatment includes the following steps: fixing the alloy rod with the surface sprayed with the treatment slurry with a bracket, suspending it in an oven, adjusting the temperature to 150-175°C, drying it for 10-15 minutes, then transferring it to a muffle furnace, adjusting the temperature to 835-840°C, firing it for 2-2.5 minutes, and then transferring it to a 100°C oven for treatment for 1.5-2 hours.
6. The method for processing the surface coating of a contact material according to claim 1, characterized in that: The average thickness of the first coating layer is 25 micrometers, and the average thickness of the second coating layer is 32 micrometers.
7. A surface coating obtained by the treatment method according to any one of claims 1 to 6.
Citation Information
Patent Citations
High-voltage isolating switch contact with good service life
CN116417268A
Electrical conductors having organic compound coatings
CN102760515A
Production method for electrical contact material
CN1594669A